2004
DOI: 10.1152/ajpregu.00496.2003
|View full text |Cite
|
Sign up to set email alerts
|

What sets the long-term level of sympathetic nerve activity: is there a role for arterial baroreceptors?

Abstract: Malpas, Simon C. What sets the long-term level of sympathetic nerve activity: is there a role for arterial baroreceptors? Am J Physiol Regul Integr Comp Physiol 286: R1-R12, 2004; 10.1152/ajpregu.00496.2003.-Much of our knowledge of the influence of the sympathetic nervous system on the control of blood pressure is built on experimental approaches that focus very much on time scales Ͻ24 h. Although direct recordings of sympathetic nerve activity (SNA) over short time scales provide important information, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 93 publications
3
40
1
1
Order By: Relevance
“…Because technical limitations have precluded an understanding of the role of baroreflexes in long-term control of sympathetic activity and arterial pressure, the present findings are particularly important because they present a perspective that is diametrically opposite from studies using SAD. Furthermore, they are consistent with emerging evidence that the natural activation of the baroreflex in hypertension has sustained effects on cardiovascular function by chronically inhibiting sympathetic activity (1,13,17,19).…”
Section: Perspectivessupporting
confidence: 87%
See 1 more Smart Citation
“…Because technical limitations have precluded an understanding of the role of baroreflexes in long-term control of sympathetic activity and arterial pressure, the present findings are particularly important because they present a perspective that is diametrically opposite from studies using SAD. Furthermore, they are consistent with emerging evidence that the natural activation of the baroreflex in hypertension has sustained effects on cardiovascular function by chronically inhibiting sympathetic activity (1,13,17,19).…”
Section: Perspectivessupporting
confidence: 87%
“…Both modifications were based on the arterial pressure and sympathetic responses to SAD, the most commonly used approach for studying the role of the baroreflex in long-term control of arterial pressure. The transient sympathetic activation and hypertension following SAD are often interpreted to indicate the unimportance of baroreflexes in long-term control of arterial pressure (4,13,17,19). In marked contrast, studies during 1 wk of electrical stimulation of the carotid sinus demonstrate a sustained effect of baroreflex activation to suppress sympathetic activity and arterial pressure.…”
Section: Protocol Modificationsmentioning
confidence: 99%
“…In this regard, there has been a long-standing controversy as to whether baroreflexes play a role in the pathogenesis of hypertension. 9,13,14 This controversy stems from the paucity of techniques available to assess the long-term effects of the baroreflex on sympathetic activity, organ function, and arterial pressure. Solid arguments have been advanced to discount the role of baroreflexes in long-term control of sympathetic activity and arterial pressure.…”
mentioning
confidence: 99%
“…We propose that these be used as the standard equations for calculating threshold and saturation values when a logistic sigmoid function is used to model the open-loop baroreflex function curve. mathematical modeling; input-output relationship; baroreflex operating range; regression analysis THE BARORECEPTOR REFLEX is the major feedback control system regulating arterial blood pressure in the short term (5,14), and possibly also in the longer term (15,27). Numerous studies in humans and animals have demonstrated that the baroreceptor reflex can be reset under physiological conditions such as exercise (6 -8, 12, 17, 19 -24, 26, 28), sleep (18), heat stress (3), or pregnancy (4) and also pathological conditions such as hypertension (9,11) and cardiovascular deconditioning (10).…”
mentioning
confidence: 99%